PENGARUH PENGGUNAAN TELUR INFERTIL DALAM RANSUM AYAM KAMPUNG SUPER TERHADAP BOBOT POTONG, KARKAS, NON KARKAS, PERSENTASE KARKAS DAN NON KARKAS: EFFECT OF INFERTILE EGGS IN FEED ON SLAUGHTER WEIGHT, CARCASS, NON CARCASS, PERCENTAGE CARCASS AND NON CARCASS ON SUPER NATIVE CHICKEN - Suprayogi, Wara Praritis Sabar; Rahma, Salma Aulia; Akhirini, Novi; Saputro, Wahyu Subagio; Darmawan, Muhammad Arif; Saraswati, Pramita Nindya; Yano, Aan Andri (Tropical Animal Science, 2024)
This study aimed to determine the effect of infertile eggs in the feed on slaughter weight, carcass quality and non-carcass quality in super native chickens. A total of 40 super-male chickens aged eight weeks were used in this study. The design of this study used a completely randomized design with a directional pattern with 4 treatments and 5 replications. The treatments in this study included: P0 (100% basal feed without additional infertile eggs); P1 (basal feed 96,7% + 3,3% infertile eggs); P2 (basal feed 93,4% + 6,6% infertile eggs) and P3 (basal feed 90,1% + 9,9% infertile eggs). The data were using analysis of variance (ANOVA), if significant results were obtained, they would be tested using Duncan's Multiple Range Test (DMRT). The results showed that the use of infertile eggs into the feed up to a level of 9.9% could increase the slaughter weight, carcass weight and carcass percentage (P<0.05). The addition of infertile eggs up to the level of 9.9% can also reduce the percentage of non-carcasses in super native chickens (P<0.05). The conclusion of this study is that infertile eggs can be used as feed ingredients for feed up to a level of 9.9% to increase slaughter weight, carcass weight, carcass percentage and can reduce the percentage of non-carcass in super native chickens.